MR Imaging of Papillary Tumor of the Pineal Region - Chang, A.H.; Fuller, G.N.; Debnam, J.M.; Karis, J.P.; Coons, S.W.; Ross, J.S.; Dean, B.L. (American Journal of Neuroradiology, 2008)
SUMMARY: We report the imaging features of 4 cases of patients with papillary tumor of the pineal region, a tumor newly recognized in the 2007 World Health Organization “Classification of Tumors of the Nervous System.” In each case, the tumor was intrinsically hyperintense on T1-weighted images with a characteristic location in the posterior commissure or pineal region. The pathologic hallmarks of the tumor are discussed, including a possible explanation for the MR imaging characteristics in our cases.